اكتساب الثقافة العربية من خلال برنامج الانغماس اللغوي لدى أساتذة جامعة مولانا مالك إبراهيم مالانج - Makhi Ulil Kirom; Dien Nur Chotimah; Mowafg Masuwd (UIN Maulana Malik Ibrahim Malang, 2026)
Many Arabic language learners struggle to use the language effectively in Arab societies due to a limited understanding of Arab culture. This study explores the impact of the Lisan Al Arab linguistic immersion program on Arabic language acquisition and cultural awareness among professors at Maulana Malik Ibrahim State Islamic University in Malang. Employing a qualitative descriptive approach, data were collected through in-depth interviews with program participants and analyzed to identify patterns in language proficiency and cultural adaptation. Findings show that the program significantly improved participants’ Arabic language skills, especially in fluency and confidence using the language in real-world contexts. Daily interaction with native speakers in natural linguistic environments played a key role, as did cultural activities such as visits to historical sites and participation in social events. These experiences deepened participants' understanding of Arab values and customs, reinforcing the cultural context of their language use. The study highlights supporting factors essential to the program’s success, including high-quality teaching, an engaging learning atmosphere, and opportunities for practical communication. Challenges were also noted, particularly in the early stages, such as adapting to local dialects and fast-paced conversations. Overall, the research concludes that immersion programs in Arab societies effectively enhance both linguistic and cultural competence among Arabic language educators.